Yeats, Pound and their Brazilian translations - Mateus, Andréa Martins Lameirão (ABEI Journal, 2015)
From the second half of the last century on, we have seen a certain number of translations of English language poetry into Brazilian Portuguese. Some of these are landmarks in the field of poetic translations in Brazil. The aim of this article is to present a preliminary investigation and comparison of the effect that translation choices had in the reception of two authors, namely, William Butler Yeats and Ezra Pound. Another point in the investigation is the longevity of these translations in the catalogues of their publishers. Availability, scope, quality and intention play a role in the way Yeats and Pound were translated and how they were read in Brazil.Keywords: Translation; poetic translation; English language poetry;reception.